PATHOPHYSIOLOGICAL MECHANISMS AND CLINICAL EVIDENCE OF CARDIAC ARRHYTHMIAS ASSOCIATED WITH ENERGY DRINK CONSUMPTION: A COMPREHENSIVE SYSTEMATIC REVIEW - Michalska, Paulina; Przybylska, Zuzanna; Purpura, Aleksandra Anna; Rolski, Wiktor; Przystaś, Bartłomiej; Hobot, Mikołaj Piotr; Dobosz, Gabriela Patrycja; Podeszwa, Sebastian; Grzechowiak, Magdalena; Michalski, Paweł (International Journal of Innovative Technologies in Social Science, 2026)
Background: Energy drinks (EDs) are widely consumed beverages containing high concentrations of caffeine, taurine, and stimulants. Popular among adolescents and athletes, EDs may exert significant cardiovascular effects, including autonomic and electrophysiological alterations that increase susceptibility to arrhythmias.Aim: This review synthesized evidence on mechanisms and clinical findings associated with cardiac arrhythmias triggered by ED consumption.Materials and Methods: A search was conducted via PubMed, MDPI, and Google Scholar (2014 onwards). Keywords included “energy drinks”, “caffeine”, “ECG”, and “cardiac arrhythmia”. Analysis focused on human studies evaluating cardiovascular and autonomic effects of ED intake.Results: ED consumption induces acute hemodynamic and electrophysiological changes, such as increased heart rate, elevated blood pressure, QTc interval prolongation, and altered heart rate variability. These effects are mediated by caffeine-induced adenosine receptor antagonism, catecholamine release, and enhanced myocardial excitability. Additional ingredients, like taurine and sugars, influence ion channel activity and autonomic balance, promoting sympathetic predominance. Supraventricular and ventricular arrhythmias are temporally associated with ED intake, particularly in individuals with underlying cardiovascular disease or genetic syndromes.Conclusions: EDs promote arrhythmogenic conditions through autonomic, hemodynamic, and electrophysiological mechanisms. While occasional intake in healthy individuals is unlikely to cause significant arrhythmias, excessive consumption in susceptible populations increases risk. Further studies are needed to define safe consumption thresholds.